A Certificateless Ring Signature Scheme with High Efficiency in the Random Oracle Model. (21st June 2017) - Zhang, Yingying; Zeng, Jiwen; Li, Wei; Zhu, Huilin
Abstract : Ring signature is a kind of digital signature which can protect the identity of the signer. Certificateless public key cryptography not only overcomes key escrow problem but also does not lose some advantages of identity-based cryptography. Certificateless ring signature integrates ring signature with certificateless public key cryptography. In this paper, we propose an efficient certificateless ring signature; it has only three bilinear pairing operations in the verify algorithm. The scheme is proved to be unforgeable in the random oracle model.